Role of Digital Banking Services in Enhancing Customer Trust: A Case of Kathmandu Valley - Thakur, Suvash (Nepalese Journal of Finance, 2025)
This study examines the role of digital banking services in enhancing customer trust: A case of Kathmandu Valley. Customer trust is the dependent variable. The selected independent variables are transaction security, service quality, user experience, privacy protection, and ease of use. The primary sources of data are used to assess the opinions of respondents regarding transaction security, service quality, user experience, privacy protection, ease of use, and customer trust. The study is based on the primary data of 144 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the role of digital banking services in enhancing customer trust: A case of Kathmandu Valley. The study showed a positive impact of transaction security on customer trust. It indicates that high standard transaction security-based system leads to increase the customer trust. Similarly, the study showed a positive impact of service quality on customer trust. It indicates that better service quality of mobile banking leads to increase the customer trust. Likewise, the study showed a positive impact of user experience on customer trust. It indicates that effective user experience mechanism leads to increase the customer trust. Further, the study also showed a positive impact of privacy protection on customer trust. It indicates that better the privacy protection, higher would be the customer trust. Moreover, the study showed a positive impact of ease of use on customer trust. It indicates that adaptive ease of use leads to increase the customer trust.